A National Survey Identifying the Factors Associated With Cardiovascular Care Nurses' Perceived Knowledge of International Practice Guidelines: The First Step in the Development of an Implementation Strategy. Issue 4 (July 2021) - McKee, Gabrielle; Hayes, Maria; Caples, Norma; Lowry, Avril; Shine, Maria; Hannon, Bernadette; Cronin, Edel; Lodge, Emer; Hill, Loreena; Tuohy, Margaret; Gillen, Nessa; Teehan, Sinead
Abstract : Background: The implementation of international guidelines within everyday practice remains problematic, which can have a detrimental impact on quality of care delivered. This study aimed to ascertain the factors associated with clinical nurses' perceived knowledge of international guidelines. Methods: In this cross-sectional survey, nurses from 45 hospitals across Ireland were recruited. A previously validated anonymous questionnaire that assessed guideline knowledge, use, and barriers to implementation was used. Data were analyzed using SPSS 23 and logistic regression. Results: Of the 542 responses, 54% had used international guidelines relevant to their practice and 50% had consulted within the last year. Most nurses perceived that poor patient follow-up, lack of time and resources, poor clinical leadership, workload, long guidelines, and not understanding guideline detail were barriers to guideline use and implementation. Forty-five percent rated their perceived knowledge of guidelines as "low." Logistic regression identified that "high" knowledge levels were significantly associated with having read guidelines in the last year and their use with practice. In contrast, low knowledge of the guidelines was associated with perceptions that they were lengthy and not easy to use, lack of confidence to challenge colleagues when guidelines are not implemented, or not being able to influence current practice. Conclusions: This study identified the specific knowledge needs in this cohort of mainly basic grade registered nurses, with low perceived guideline knowledge. A whole unit or team approach led by nurse champions is needed to develop and establish practice and educational strategies that would increase the availability, application, and knowledge of guidelines within everyday practice. Abstract : Supplemental digital content is available in the text.